ANALISIS KEPUASAN KONSUMEN TERHADAP KUALITAS PRODUK DAN PELAYANAN MANGSI GRILL AND COFFEE DENPASAR - Mandasari, Dian; Mulyani, Sri; Sadyasmara, Cokorda Anom Bayu (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI, 2019)
The Aims of this research were to : (1) find out which of the product and service attributes that considered important by the customer to achieve customer satisfaction on product and service quality in Mangsi Grill And Coffee, (2) Calculate customer satisfaction level on product and service quality in Mangsi Grill And Coffee (3) To determine attributes that need to get priority from Mangsi Grill And Coffee according to the importance and performance level in giving satisfaction to customer in Mangsi Grill And Coffee. This research applied Customer Satisfaction Index (CSI) and Potential Gain In Customer Values (PGCV). The Result of the research showed that all of the service quality attributes considered important by the customer and so does for the 18 of 20 product quality attributes. The level of customer satisfaction based on CSI for service quality is 85% and on product quality is 82%, which shows that consumers are very satisfied with products and services at Mangsi Grill and Coffee. Service quality attributes that need to gain attention are employee appearance with indeks of PGCV 3.739; interior design with indeks of PGCV 3.73 5; internet availability (wifi) with indeks of PGCV 3.657; and equipments with indeks of PGCV 3.614, while product quality attributes that need to gain priority are food presentation with indeks of PGCV 3.759; the beverage presentation with indeks of PGCV 3.569 ; discount with indeks of PGCV 3.458 and social media application with indeks of PGCV 3.327. Keywords : coffee, product quality, service quality, customer satisfaction, Customer Satisfaction Index (CSI), Potential Gain In Customer Values (PGCV)